Perceived justice, service satisfaction and behavior intentions following service recovery efforts in a South African retail banking context. Issue 2 (3rd April 2017) - Petzer, Daniel J.; De Meyer-Heydenrych, Christine F.; Svensson, Göran
Abstract : Purpose: The interactional and distributive dimensions of perceived justice as one of its objectives are to reveal the link between perceived justice and service satisfaction (SS). The purpose of this paper is to consider the influence of the perceived justice that South African retail bank customers experience based on the service recovery efforts of these banks in response to their complaints, the customers' SS, and, consequently, the behavioral intention (BI) toward these banks. Design/methodology/approach: This study focuses on the perceived justice construct where a service failure has occurred followed by a customer complaint and a resultant service provider response. In total, 281 respondents completed a structured self-administered questionnaire. Findings: The study found that interactional and distributive justice (DJ) experienced in response to the service recovery efforts of a bank significantly and positively influence SS, and that SS in turn significantly and positively influences the BI of these customers. However, it was found that interactional and DJ had no direct effect on BI. Research limitations/implications: The research model tested addresses the interfaces between service receivers' perception of interactional justice, distributional justice and SS as well as the interface between SS and BI. The tested research model indicates that both are interrelated through SS. Practical implications: It is evident from the findings that retail banks should utilize the service encounter that follows a customer complaint as a desirable prospect to implement strategies to recover from service failures in an effort to bring about perceived justice that will ultimately influence customers' levels of SS and BI. Originality/value: This study makes a complementary contribution to previous studies and existing theory building a nomological framework of constructs in service encounters consisting of service receivers' perceived justice, SS and BI.